2018
DOI: 10.3390/jfmk3030048
|View full text |Cite
|
Sign up to set email alerts
|

The Uncontrolled Manifold Concept Reveals That the Structure of Postural Control in Recurve Archery Shooting Is Related to Accuracy

Abstract: In this study, we examine the structure of postural variability in six elite-level recurve archers using the uncontrolled manifold concept. Previous research showed equivocal results for the relationship between postural control and shooting accuracy, but these studies were mainly limited to a descriptive approach to postural variability/stability and did not take the simultaneous movements of the upper limb joints into account. In this study, we show that the goal-equivalent variability which stabilizes the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…(a) shooting and air-rifle shooting (Niinimaa and McAvoy, 1983;Larue et al, 1989;Aalto et al, 1990;Era et al, 1996;Ball et al, 2003;Mononen et al, 2007;Ihalainen et al, 2016a,b;Spancken et al, 2021;Lang and Zhou, 2022a,b), air-pistol shooting (Ko et al, 2017(Ko et al, , 2018, sharpshooting (Konttinen et al, 1998(Konttinen et al, , 1999, small-bore shooting (Spancken et al, 2021); (b) biathlon (Niinimaa and McAvoy, 1983;Larue et al, 1989;Ihalainen et al, 2018;Michalska et al, 2022); (c) archery (Mason and Pelgrim, 1986;Stuart and Atha, 1990;Mohamed and Azhar, 2012;Spratford and Campbell, 2017;Musa et al, 2018;Serrien et al, 2018;Simsek et al, 2019;Wada and Takeda, 2020;Sarro et al, 2021;Vendrame et al, 2022); (d) gymnastics (Bringoux et al, 2000;Vuillerme et al, 2001a,b;Aydin et al, 2002;Asseman et al, 2004Asseman et al, , 2005Asseman et al, , 2008Davlin, 2004;Bressel et al, 2007;Carrick et al, 2007;Croix et al, 2010;Omorczyk et al, 2018;Marcolin et al, 2019;…”
Section: Resultsmentioning
confidence: 99%
“…(a) shooting and air-rifle shooting (Niinimaa and McAvoy, 1983;Larue et al, 1989;Aalto et al, 1990;Era et al, 1996;Ball et al, 2003;Mononen et al, 2007;Ihalainen et al, 2016a,b;Spancken et al, 2021;Lang and Zhou, 2022a,b), air-pistol shooting (Ko et al, 2017(Ko et al, , 2018, sharpshooting (Konttinen et al, 1998(Konttinen et al, , 1999, small-bore shooting (Spancken et al, 2021); (b) biathlon (Niinimaa and McAvoy, 1983;Larue et al, 1989;Ihalainen et al, 2018;Michalska et al, 2022); (c) archery (Mason and Pelgrim, 1986;Stuart and Atha, 1990;Mohamed and Azhar, 2012;Spratford and Campbell, 2017;Musa et al, 2018;Serrien et al, 2018;Simsek et al, 2019;Wada and Takeda, 2020;Sarro et al, 2021;Vendrame et al, 2022); (d) gymnastics (Bringoux et al, 2000;Vuillerme et al, 2001a,b;Aydin et al, 2002;Asseman et al, 2004Asseman et al, , 2005Asseman et al, , 2008Davlin, 2004;Bressel et al, 2007;Carrick et al, 2007;Croix et al, 2010;Omorczyk et al, 2018;Marcolin et al, 2019;…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the 8-post movement is called a circuit, then after the athlete has done one circuit, they are given a break of about 3 minutes (Fahrizqi et al, 2021). Good exercise program causes the score to increase, this can be obtained when the physical condition is supportive or is in shape and balanced with programmed exercises (Serrien et al, 2018). In line with providing structured and consistent training can increase accuracy especially in target sports (Pratiwi & Mansur, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies assessing the impact of upper limb positions on body balance control have been included in the discussion. They mainly concern pistol, rifle, and archery athletes [ 36 , 37 , 38 , 39 ]. Research conducted on shooters has shown that the rearing of the body affects the effectiveness of shooting with a pistol but not with a rifle.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted on shooters has shown that the rearing of the body affects the effectiveness of shooting with a pistol but not with a rifle. Serrien et al showed that, for elite archers, it is not necessary to minimize the degrees of freedom of all movements when aiming, but rather to take advantage of the structure of the kinematic chain variation [ 37 ]. Mon et al concluded that balance played different roles in shooting disciplines [ 39 ].…”
Section: Discussionmentioning
confidence: 99%